2008
DOI: 10.4049/jimmunol.181.10.7332
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Scavenger Receptor Class B Type I Is Critical for Simvastatin Enhancement of High-Density Lipoprotein-Induced Anti-Inflammatory Actions in Endothelial Cells

Abstract: Changes in plasma lipoprotein profiles, especially low levels of high-density lipoprotein (HDL), are a common biomarker for several inflammatory and immune diseases, including atherosclerosis and rheumatoid arthritis. We examined the effect of simvastatin on HDL-induced anti-inflammatory actions. HDL and sphingosine 1-phosphate (S1P), a bioactive lipid component of the lipoprotein, inhibited TNF α-induced expression of VCAM-1, which was associated with NO synthase (NOS) activation, in human umbilical venous en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 50 publications
4
29
0
1
Order By: Relevance
“…The S1P content in the rHDL and cholesterol-loaded rHDL was undetectable by our S1P assay method (22). The sources of all other reagents were described previously (19,23,24). Unless otherwise stated, S1P (1 M), rHDL (500 g protein/ml), and native HDL (500 g protein/ ml) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The S1P content in the rHDL and cholesterol-loaded rHDL was undetectable by our S1P assay method (22). The sources of all other reagents were described previously (19,23,24). Unless otherwise stated, S1P (1 M), rHDL (500 g protein/ml), and native HDL (500 g protein/ ml) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…HDL is reported to inhibit VCAM-1 expression in endothelial cells (4) in an SR-B1-specific manner (44). We hypothesized that MPO-dependent oxidative modification of HDL may inhibit this antiinflammatory and atheroprotective activity of HDL.…”
Section: Mpo-dependent Oxidation Of Hdl Inhibits the Anti-inflammatormentioning
confidence: 99%
“…In vitro experiments have indeed shown that statin-mediated improvement of endothelial function is due to a direct effect of the drug on endothelial cells. Incubation of endothelial cells with different statins promotes a significant increase expression of SR-BI and S1P receptors and of eNOS, with a consequent increased production of NO after incubation with HDL (Igarashi et al 2007;Kimura et al 2008). A recent study performed on subjects with isolated low HDL-C showed that FMD was significantly improved after 4 weeks treatment with pravastatin, and multiple regression analysis revealed that changes in HDL-C and EPC number were independent predictors of FMD increase (Higashi et al 2010).…”
Section: Statinsmentioning
confidence: 99%